(3CWHGb GdPgHs - (3GdCUagGfj, TQa GdOjf, YHO GdeDef Hf gHI Gddg, J (B600(3g`s
(3ChdgG (B:s
(3Gddge EfG fMeOc Ydi eG CSHdJ ef LdGHjH cQechHYO abO CTGQ Edj hdj ef ChdjGA GddgCMeO Hf eMehO GdNhJj Cf CLeY dg eGFI ebGdI aj GdhYX hGdfUjMI hGdNWHhSejJgG CWHGb GdPgHs
(3BNQgG (B:s
(3aUGM JaQbJ CLRGDgG Ydi LHGd GdbOS aVegf hEP GHJdi EHQGgje QHg HcdeGJ aCJegf, Gddge Upqd Ydi eMeO hYdi Bd eMeO hSdes
(3Hjf CSWQg JYdjbGJ HGdeOGO GdCMeQ HGddZI GdaGQSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 170s
(3cTa GdXfhf(B: 1/ 116s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs